To convert the equation from vertex form \( y = -4(x + 5)^2 - 3 \) to standard form, we will first need to expand the equation.
-
Expand the square: \[ (x + 5)^2 = x^2 + 10x + 25 \]
-
Substitute back into the equation: \[ y = -4(x^2 + 10x + 25) - 3 \]
-
Distribute \(-4\): \[ y = -4x^2 - 40x - 100 - 3 \]
-
Combine like terms: \[ y = -4x^2 - 40x - 103 \]
Thus, the equation in standard form is:
\[ y = -4x^2 - 40x - 103 \]
The correct response is: y = -4x^2 - 40x - 103 (y equals negative 4 x squared minus 40 x minus 103).